Technologies for Fabricating Large-Size Diffraction Gratings - Changfeng Shao; Xinghui Li (Sensors)
Large-size diffraction gratings have played an important role in modern scientific fields such as inertial confinement fusion, large-aperture astronomical telescopes, and high-precision immersion lithography machines with long-stroke displacement stages. However, due to the large size and high accuracy requirements of gratings, and considering the need for high efficiency and low cost, the fabrication of large gratings is extremely difficult. This paper reviews the fabrication technologies for large diffraction gratings, including grating tiling technology, grating ruling technology, single-exposure lithography, optical mosaic grating technology, and scanning beam interference lithography. It introduces the basic principles, representative research, and research progress of these technologies, analyzes their advantages and current problems, and provides reference for the development and optimization of the fabrication technologies of large diffraction gratings.